A Study on Antioxidant Properties of Hypoglycaemic Plants: Exploring the Therapeutic Potential of Hypoglycaemic Plants (Journal of Advances and Scholarly Researches in Allied Education, 2023)
For health care systems, natural products are crucial. The numerous sources of plants andherbal substances have been exploited to create chemical compounds that are employed as raw materialsin the creation of pharmaceuticals and other types of treatments. Since the development process from theplant to a purified, pharmacologically active component is extremely arduous and drawn out, amultidisciplinary approach is necessary. Despite the significance of contemporary medicines, the marketfor herbal cures is continuously expanding. The strong and effective herbal medicines need to beexamined using established scientific methods in order to be validated for the treatment of ailments. Dueto current patent laws, it is more important than ever to safeguard the claims of these time-testedtraditional remedies. It is now essential to begin cataloguing the components and processes of thesemedicinal plants.